Evaluation of surgical treatment of recent diaphyseal fractures of the humerus in adults based on 42 cases - Hachim, Mohamed; Daffe, Mohamed; Camara, Ibrahima Sory; Sow, Diarga; A., Ousmane B. (International Journal of Research in Orthopaedics, 2025)
Background: Humeral shaft fractures (HDF) in adults account for 2% of all fractures. Surgical treatment can be either closed or open. Methods: This was a retrospective, descriptive and evaluative study conducted from January 2020 to December 31, 2023, at Centre Hospitalier National Matlaboul Fawzaini de TOUBA (CHNMFT) on 42 cases. The exclusion criteria were all patients under 15 years of age receiving orthopaedic treatment. Results: The average age of our patients was 40 years, with a male predominance. The most common circumstances were road traffic accidents (32 cases). According to the AO classification, type A fractures were the majority (32 cases). According to the surgical technique, pinning was the most common (22 cases). No complications were noted and all our patient’s achieved union within 12 to 24 weeks. At a mean follow-up of 13.5 months, according to the modified Stewart and Hundley classification, 61% of our patients were classified as Good versus 32% as Very Good. Conclusions: FDHs in adults are very common. The radial nerve remains the dread of every surgeon and surgical treatment yields the best results.